Literary and Cultural Narratives of Agricultural Transformation in Modern Chhattisgarh - Sinha, Sujita (Journal of Advanced Research in Humanities and Social Sciences; Vol 12 No 3 (2025): Journal of Advanced Research in Humanities and Social Sciences, 2025)
This article delves into the intricate relationship between agricultural transformation and its representation in the literary and cultural landscape of modern Chhattisgarh. Examining a range of literary forms, including novels, poetry, short stories, and oral traditions, alongside cultural expressions such as folk songs, rituals, and visual arts, this study analyzes how the socio-economic shifts in agriculture are narrated, interpreted, and contested within the region’s cultural fabric. It investigates the impact of modernization, technological advancements, agrarian policies, and environmental changes on the lives and livelihoods of agricultural communities, as reflected in their creative outputs. Furthermore, the article explores how these narratives shape collective identities, preserve historical memory, and articulate aspirations for the future. By employing a multidisciplinary approach that combines literary criticism, cultural studies, and insights from agrarian sociology, this research aims to provide a nuanced understanding of the human dimensions of agricultural change in Chhattisgarh. It highlights the role of storytelling and cultural practices in mediating experiences of transformation, fostering resilience, and envisioning alternative agrarian futures.